A dynamic layer management scheme for a superpeer ring with a loosely-consistent DHT. (11th September 2008) - Han, Saeyoung; Park, Sungyong
In this paper we propose a Dynamic Layer Management (DLM) scheme for a self-organising superpeer ring with a loosely-consistent DHT. Each peer estimates the global capacity based on the information collected by mobile agents and autonomously decides whether it can be a superpeer or not. The proposed scheme also changes the size of the superpeer ring adaptively according to the size of the network, and maintains an appropriate number of superpeers in dynamic peer-to-peer environments. The benchmarking results show that our scheme outperforms the fixed superpeer system in terms of search latency at the expense of message overhead added for the DLM.